Effectiveness of health education intervention on intention not to perform female genital mutilation/cutting in the future among key decision-makers: a systematic review and meta-analysis - Wubareg Seifu; Tesfaye Assebe Yadeta; Girum Shibeshi Argaw; Eyob Wubishet Abebe; Abdulahi Siraj Abdi; Seid Yimam Ali; Nega Assefa (BMC, 2024)
Abstract Background Female Genital Mutilation/Cutting (FGM/C) is a form of gender-based violence that has negative health consequences. The decision to perform FGM/C is often made collectively and a variety of actors influence the decision. There is inconsistent and inconclusive evidence that health education interventions lead behavioural changes related to FGM/C among key decision-makers. Therefore, the aim of this systematic review and meta-analysis was to examine the effectiveness of health education interventions on decision-makers intentions not to perform FGM/C in the future. Methods A systematic review and meta-analysis were performed according to the Preferred Item for Systematic Review and Meta-analysis (PRISRMA) guideline. Studies were obtained from databases such as PubMed, Google Scholar, EMBASE, CINAHL, Cochrane, African Journals Online and relevant lists of identified studies (interventional studies related to FGM/C among key decision-makers). Unpublished sources and organizational websites were also searched for relevant articles. The quality of studies was assessed using the Quality Assessment Tool for Quantitative Studies developed by the Effective Public Health Practice Project's. The meta-analysis was carried out using STATA.17 and Review Manager 5.3 software. Heterogeneity and publication bias were assessed using the I2 statistic and funnel plot, respectively. The pooled effect size with a 95% confidence interval was presented using a forest plot and random effect model. Results This meta-analysis included nineteen studies with a total of 13,326 study participants. The overall pooled relative risk of intention not to perform FGM/C in the future was 1.55 (95% CI;1.24, 1.94). In the subgroup analysis, the effect of health education on intention not to perform in the future was higher in studies that used both health education and other interventions (RR = 3.75, 95% CI; 2.04, 6.88) compared to those using only health education (RR = 1.35, 95% CI; 0.95, 1.92). Studies with longer intervention duration (above 12 months) had a greater effect on intention not to perform (RR = 1.34, 95% CI; 0.86, 2.09) compared to studies with a short intervention period (6-12 months) (RR = 1.14, 95% CI; 0.61, 2.15). Conclusion This review examined the impact of health education on key decisions-makers' intention not to perform FGM/C in the future. Although the pooled effect size estimate may have been influenced by heterogeneity, the results suggest that education about FGM/C has a positive influence on the intentions of key decision-makers. It is recommended that health education interventions target local decision-makers such as religious and clan leaders and include them in initiatives aimed at preventing and eliminating FGM/C. PROSPERO registration number CRD42024542541.